COOLHAIR: a prospective randomized trial to investigate the efficacy and tolerability of scalp cooling in patients undergoing (neo)adjuvant chemotherapy for early breast cancer - Smetanay, Katharina; Junio, Philippe; Feißt, Manuel; Seitz, Julia; Hassel, Jessica C.; Mayer, Luisa; Matthies, Lina; Schumann, Arina; Hennigs, André; Heil, Jörg; Sohn, Christof; Jäger, Dirk; et al. (Breast cancer research and treatment, 2019)
PURPOSE: Chemotherapy-induced alopecia (CIA) is a distressing side effect for women with breast cancer undergoing chemotherapy. Scalp cooling is a method aiming to prevent CIA, but its efficacy is not well defined. Randomized trials until recently and at the time this trial was designed have been lacking. - METHODS: Patients undergoing (neo)adjuvant chemotherapy for early breast cancer (EBC) were randomized to scalp cooling (CAP) or observation (NoCAP). All patients received 18-24 weeks of anthracycline- and/or taxane-based chemotherapy. The primary endpoint was patient-reported rate of alopecia according to a modified version of the Dean Scale. Hair preservation was defined as hair loss ≤ grade 2 (≤ 50%). Secondary endpoints were rate of alopecia determined by medical staff, rate of wig/scarf use, tolerability as well as quality of life (QoL). - RESULTS: Seventy-nine patients were randomized. Hair preservation was observed in 39.3% of patients in the CAP arm versus 0% in the NoCAP arm (p < 0.001). Wig/scarf use was significantly less frequent in the CAP group (40.7% vs 95.5% outside home before cycle 3, p < 0.001). The drop-out rate was 31.7% and 34.2% in the CAP and NoCAP arm, respectively. Main reasons for drop-out were hair loss, adverse events (CAP), and randomization into control arm. We observed no differences in efficacy between anthracycline-based and non-anthracycline-based regimens. QoL did not differ between the study arms. - CONCLUSIONS: This trial adds to the evidence that scalp cooling effectively prevents CIA in a meaningful number of patients. This option should be made available for patients undergoing (neo)adjuvant chemotherapy for EBC.
First online: 25 September 2018
Gesehen am 27.06.2019